2004
DOI: 10.1021/es049620g
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Organic Compounds in an Eastern Arctic Marine Food Web

Abstract: An eastern Arctic marine food web was analyzed for perfluorooctanesulfonate (PFOS, C8F17SO3-), perfluorooctanoate (PFOA, C7F15COO-), perfluorooctane sulfonamide (PFOSA, C8F17SO2NH2), and N-ethylperfluorooctane sulfonamide (N-EtPFOSA, C8F17SO2NHCH2CH3) to examine the extent of bioaccumulation. PFOS was detected in all species analyzed, and mean concentrations ranged from 0.28 +/- 0.09 ng/g (arithmetic mean +/- 1 standard error, wet wt, whole body) in clams (Mya truncata) to 20.2 +/- 3.9 ng/g (wet wt, liver) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
295
7
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(339 citation statements)
references
References 35 publications
31
295
7
6
Order By: Relevance
“…The results were slightly higher than those detected in south China and eastern Arctic, 18,29 but PFOA concentration levels were lower than those found in Tokyo Bay and the Ariake Sea in Japan. 17,30 As far as we know, past studies have not reported specifically high levels of PFCs in clams; PFOA was not detectable in clams in the eastern Arctic, 29 and PFOA concentrations in clams were similar to other species in the Ariake Sea. 30 However, in this present study, clams were found to contain significantly higher concentrations of PFOA than other species (Table 1 and Fig.3-a).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The results were slightly higher than those detected in south China and eastern Arctic, 18,29 but PFOA concentration levels were lower than those found in Tokyo Bay and the Ariake Sea in Japan. 17,30 As far as we know, past studies have not reported specifically high levels of PFCs in clams; PFOA was not detectable in clams in the eastern Arctic, 29 and PFOA concentrations in clams were similar to other species in the Ariake Sea. 30 However, in this present study, clams were found to contain significantly higher concentrations of PFOA than other species (Table 1 and Fig.3-a).…”
Section: Discussionmentioning
confidence: 71%
“…The metabolic capabilities have been shown to influence the concentration of several organic pollutants in seabirds. 29 Among the eleven species, only Neverita didyma and Rapana venosa are detrivorous, while the others are all filter feeders, feeding mainly on unicellular algae, microorganisms and marine humus. It is assumed that PFCs can bioaccumulate along the food web, 27 but Neverita didyma and Rapana venosa were found to contain very low levels of PFOA and PFOS (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…0.3 [96] Narwhal, Canadian Arctic (Ellesmere Island), 2000, n ¼ 5 10.9 0.9 6.2 [96] Beluga whale, Canadian Arctic (Baffin Island), 1996, n ¼ 5…”
Section: Pfc Pattern In Marine Mammalsmentioning
confidence: 99%
“…1.6 20.9 [96] Beluga [98] Polar bear, USA (Alaska), 1990s, n ¼ 17 180-680 [119] Polar bear, USA (Alaska, Beaufort Sea), 1993-2000, n 2.5 [100] (Continued)…”
Section: Pfc Pattern In Marine Mammalsmentioning
confidence: 99%
“…Regulatory efforts are underway to limit the use of some of these chemicals, mainly the perfluorinated compounds (PFCs), due to concerns over their environmental persistency, bioaccumulation ability and toxicity [3,4]. Among the PFCs, perfluorosulfonates (PFSAs) and perfluorocarboxylates (PFCAs) are most widely detected in human [5,6] and other biological samples including those in pristine areas such as the Arctic [7,8]. Airborne fluorotelomer alcohols (FTOHs) have attracted considerable attention mainly due to their abilities for long range atmospheric transport [9,10] and can act as volatile precursors that may undergo degradation to form PFCAs and other related compounds [11,12].…”
Section: Introductionmentioning
confidence: 99%